Human-Large Carnivores Co-existence in Europe – A Comparative Stakeholder Network Analysis - Grossmann, Carol M.; Patkó, László; Ortseifen, Dominik; Kimmig, Eva; Cattoen, Eva-Maria; Schraml, Ulrich (Frontiers in Ecology and Evolution, 2020)
Improving human co-existence with large carnivores (LC) is considered necessary for reaching one of the goals of the EU Council Directive on the conservation of natural habitats and of wild fauna and flora (1992). This study is part of the EU LIFE project EuroLargeCarnivores, providing a scientific analysis of current stakeholder networks of the project partners (mainly WWF offices), a necessary foundation for “Improving human co-existence with large carnivores in Europe through communication and transboundary cooperation”. We conducted systematic participatory and transdisciplinary primary research in 14 European countries. The transdisciplinary research design consists of three phases: stakeholder identification (Phase 1), participatory stakeholder-mapping (Phase 2a), a comparative network analysis (Phase 2b), and an Individual Stakeholders’ Perception Survey (Phase 3). We use the realistic method based on perceptions of the stakeholders involved. Phase 1 identifies 10 relevant Stakeholder Categories and specific agents. Phase 2a provides distinct comprehensive regional stakeholder maps with a special focus on the quality of multilateral relationships and stakeholders which are not yet actively involved in the networks. Phase 2b concludes with a comparative network analysis. The composition, density and quality of stakeholder networks as well as the interconnectivity of the project partners differ substantially. We reveal common denominators across Europe, varying relationships between stakeholder categories, and the potential positive role of foresters and veterinarians, for example. The results indicate the need for a more comparable implementation of EU regulations at national level, and for regional adaptations of support strategies for distinct stakeholders and networks. Phase 3 provides complementary insights into the involvement of the 10 Stakeholder Categories and their attitudes to large carnivore management. It also tests the institutional representation of membership in formal organizations. We challenge the perception of distinct stakeholder categories and whether involving institutional representatives in networking activities is sufficient. Based on current conflict constellations and best practice examples, we conclude with recommendations for strategic stakeholder engagement to: a) broaden and strengthen the stakeholder networks to b) improve human-human conflict management in the context of expanding large carnivore populations and their management.